Glycerol acetylation into acetins over SnO2-based bimetallic oxide catalyst - Azami, Ain Arisya; Ramli, Irmawati; Mohamad Rasid, Shera Farisya; Khairul Lail, Muhammad Shamirul; Zakaria, Mohd Rafein; Iqbal, Sarwat (Malaysian Analytical Sciences Society, 2024)
Tin oxide-based bimetallic oxide catalysts, MOx (MOx = Al2O3, TiO2, Y2O3) with a molar ratio of MOx:SnO2 of 1:1 was prepared by the solid-state method. X-ray diffraction (XRD) analysis showed that tin oxide, SnO2, was present in all samples as a cassiterite phase with a tetragonal structure. The presence of other oxides, aluminum oxide (Al2O3), titanium oxide (TiO2), yttrium oxide (Y2O3) in the respective Al2O3/SnO2, TiO2/SnO2, Y2O3/SnO2 were also identified and confirmed by X-ray fluorescence (XRF) analysis. A small exothermic peak at 480 °C and 750 °C in the differential thermal gravimetric (DTG) analysis revealed the oxidation of sub-oxide defects, took place which are very common in SnO2-based samples. Further Fourier transform infrared spectroscopy (FTIR) analysis indicated the presence of Sn-O bonds, reflecting the abundance of tin-oxygen bonds in the materials. Acidity measurements by titration showed that both TiO2/ SnO2 and Y2O3/SnO2 have the same acidity value of 0.23 mmol/g whereas Al2O3/SnO2 and monoxide SnO2 at 0.20 mmol/g. These catalysts were tested for the acetylation of glycerol to monoacetin (MA), diacetin (DA) and triacetin (TA) in a batch reactor at a molar ratio of glycerol: acetic acid of 1:6 w/v, a temperature of 100°C, a reaction time of 2 h and a catalyst loading of 0.5 g. The tests showed complete conversion of glycerol by all catalysts, with the selective product being mainly MA, which was 64%, 62%, 57% and 43% for Al2O3/SnO2, Y2O3/SnO2, SnO2 and TiO2/SnO2, respectively. The percentage selectivity of the more valuable products, DA + TA, was produced in the following order, TiO2/SnO2 > SnO2 > Y2O3/SnO2 > Al2O3/SnO2 with 57%, 43%, 37%, and 35%, respectively. Further analysis of TiO2/SnO2 revealed that the catalyst not only had a high acidity, but also an increased BET surface area of 9.8 m2/g compared to 8.6 m2/g for SnO2 when TiO2 was incorporated into SnO2. Analysis of the surface elements by energy dispersive X-ray spectroscopy (EDX) revealed a high surface oxygen content, which is consistent with the high acidity of the sample.